1977
DOI: 10.1029/ja082i019p02650
|View full text |Cite
|
Sign up to set email alerts
|

Plasma bubbles and irregularities in the equatorial ionosphere

Abstract: Using the Atmosphere Explorer satellite AE‐C, we observe large‐scale (10‐ to >200‐km) irregular biteouts of up to three orders of magnitude in the ion concentration Ni in the nighttime equatorial F region associated with small‐scale inhomogeneities in Ni. Similar phenomena were reported by Hanson and Sanatani but without the more complete plasma diagnostics present on AE. Simultaneous plasma velocity observations show irregular upward and westward motion of the order of 150 m s−1 associated with some of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
173
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(195 citation statements)
references
References 18 publications
22
173
0
Order By: Relevance
“…However, observations by McClure et al [1977] also indicate ionospheric ion density "biteouts" of much larger horizontal extent (10 -> 200 km) and greater intensity (ion density depletions up to three orders of magnitude) than indicated by our small scale simulations.…”
Section: Introductionsupporting
confidence: 39%
“…However, observations by McClure et al [1977] also indicate ionospheric ion density "biteouts" of much larger horizontal extent (10 -> 200 km) and greater intensity (ion density depletions up to three orders of magnitude) than indicated by our small scale simulations.…”
Section: Introductionsupporting
confidence: 39%
“…The di erence in ascent and descent values is likely to be much enhanced during a spread F event. Thus, the present observations, which were conducted during a well-developed spread F epoch, showing maximum change in electron density by a factor of 20 around 210 km altitude, indicate the presence of enhanced horizontal electron density gradients throughout the 150±300 km altitude region during fully developed spread F. Similar horizontal gradients were observed by McClure et al (1977), in AE satellite data. Recently, Gdalevich et al (1998) reported the presence of horizontal gradients in plasma density, using a cylindrical Langmuir probe in the rocket experiment`Vertical-10', and attributed these to large-scale disturbances propagating as internal gravity waves (IGWs), in the upper atmosphere.…”
Section: Large-scale Irregularitiessupporting
confidence: 86%
“…The NRL group has also added neutral wind effects to these simulations and found that an eastward neutral wind results in a westward motion of the bubbles in addition to its rise . This is also in agreement with observations of bubble motion (see McClure et al, 1977 (14) and (15) were utilized 'with n = n + ?~, etc . This yields the following coupled nonlinear…”
supporting
confidence: 91%
“…It should be emphasized that this paper will deal only with equatorial Spread F theory and , in addition , dwell only on those theories using plasma mechanisms as a basis. For experimental results, the worXs of Farley et al (1970), Dyson et al • (1974) , Kelley et al (19 76) , Woodman and La Hoz (1976) , Morse et al (1977), and McClure et al (1977) should serve as good references for the interested reader.…”
Section: T I I I "I Ti°ji It -Introductionmentioning
confidence: 99%